Stigma Experienced by Rural Pregnant Women with Substance Use Disorder: A Scoping Review and Qualitative Synthesis - Bright, Victoria; Riddle, Julia; Kerver, Jean (International journal of environmental research and public health, 2022)
Identification and recognition of experiences of rural pregnant women with substance use disorder is needed to inform public policy and medical training. This paper reviews and qualitatively synthesizes literature exploring the experiences of this population. Embase, PubMed, and Web of Science were used to identify literature through August 2022 using the search terms, such as pregnancy, substance use or abuse, stigma, and rural. Cited and citing research were also considered. Exclusion criteria included articles that failed to consider rural pregnant women’s perspectives on stigma experienced, included potential confounds, occurred outside of the United States or Canada, and were published before January 2000. Nine articles met the inclusion criteria. Data were synthesized by the listed authors and assessed for common themes. A review of the articles revealed three common themes: stigma occurs in community settings, stigma occurs in healthcare settings, and comprehensive care is important to ensure appropriate support to this population. Stigma as a barrier seems to improve when women have strong social support and access to comprehensive care networks. Addressing this stigma through programs, such as peer social guidance and comprehensive health centers, may provide appropriate support to pregnant, rural women with SUD to further navigate their health needs.